Pneumonia Mortality Trends in Children under 5 Years of Age in the Context of Pneumococcal Conjugate Vaccination in Peru, 2003–2017 - Sanchez, Carlos A. (2023)
Worldwide, conjugated pneumococcal vaccines (PCVs) have proven effective against invasive pneumococcal disease, but non-invasive pneumonia is a major cause of mortality in young children and serotypes vary geographically, affecting effectiveness. We analyze nationwide death certificate data between 2003–2017 to assess the impact of PCVs on pneumonia mortality among young children from Peru. We report descriptive statistics and perform timeseries analysis on annual mortality rates (AMRs) and monthly frequencies of pneumonia deaths. Children under 5 years of age accounted for 6.2% (n = 10,408) of all pneumonia deaths (N = 166,844), and 32.3% (n = 3363) were children between 1–4 years of age, of which 95.1% did not report pneumonia etiology. Comparing periods before and after PCV introduction in 2009, mean AMRs dropped 13.5% and 26.0% for children between 1–4 years of age (toddlers/preschoolers), and children under 1 year of age (infants), respectively. A moderate correlation (Spearman’s r = 0.546, p < 0.01) in the monthly frequency of pneumonia deaths was estimated between both age groups. Quadratic regression suggests a change in direction around 2005 (highest pneumonia mortality) for both age groups, but percentage change analysis identified an inflection point in 2013 for infants only, not for toddlers/preschoolers, suggesting that the impact of PCVs might be different for each age group.